A critical study of false doctrine, looking into the concept and its punishments under the Syariah Criminal offences enactments in Malaysia / Mohd Efendi Mohd Razali … [et al.] - Mohd Razali, Mohd Efendi; Bohari, Mohd Adam; Mahadi, Amirul Syafiq; Mat Zin, Mohd Faiz; Zainuzzaman, Nik Mohd Faris Syazwan (Faculty of Law, 2010)
This research is a critical study on the concept of false doctrine and its punishment under the Syariah Criminal offences Enactments in Malaysia. The research which has been conducted is to show that the punishment for a person committing a deviant teaching or in law which has been defined as a false doctrine is inadequate enough since the act committed can be categorized as one of the big sin in the Quran. In addition, this research is more focusing on the punishment of false doctrine and we have set out the provisions which relating to the punishment of false doctrine from different states in Malaysia in order to compare whether the punishment for false doctrine is adequate enough or otherwise in term of it substantive law, wording, uniformity and workability. This study also concerns on how effectiveness the punishment of false doctrine provided by the Syariah law criminal offences enactment, hence, we found that the punishment that were imposed is to be said inadequate and a person who commits a false doctrine should not be worried about the punishment as he can afford to pay and bear the burden by all means which they only take for granted towards the punishment and in future they will do the same thing and it goes over and over again. Therefore, this study seek to discover the concept of false doctrine in Malaysia and also the punishment that have been imposed to it.